2017
DOI: 10.1111/pbi.12686
|View full text |Cite
|
Sign up to set email alerts
|

QTL‐seq approach identified genomic regions and diagnostic markers for rust and late leaf spot resistance in groundnut (Arachis hypogaea L.)

Abstract: SummaryRust and late leaf spot (LLS) are the two major foliar fungal diseases in groundnut, and their co‐occurrence leads to significant yield loss in addition to the deterioration of fodder quality. To identify candidate genomic regions controlling resistance to rust and LLS, whole‐genome resequencing (WGRS)‐based approach referred as ‘QTL‐seq’ was deployed. A total of 231.67 Gb raw and 192.10 Gb of clean sequence data were generated through WGRS of resistant parent and the resistant and susceptible bulks for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
195
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 187 publications
(203 citation statements)
references
References 43 publications
(93 reference statements)
4
195
0
Order By: Relevance
“…The two major QTLs for ELS on LG B03 were flanked by homeologous markers from chromosome A03, suggesting that these regions of chromosome A03 may constitute a hot spot for genes responsible for ELS resistance. In a recent study using QTL‐seq approach in a TAG24 × GPBD4 RIL population, a 2.98 Mb (131.67–134.65 Mb) genomic region on chromosome A03, which overlaps with the region indicated in the present study to contain these two major ELS‐resistant QTLs (132.10–132.20 Mb and 133.65–133.73 Mb, respectively), was also found to contribute to LLS resistance (Pandey et al ., ). This supports the notion that this region on chromosome A03 has genes playing role in defence against leaf spots.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The two major QTLs for ELS on LG B03 were flanked by homeologous markers from chromosome A03, suggesting that these regions of chromosome A03 may constitute a hot spot for genes responsible for ELS resistance. In a recent study using QTL‐seq approach in a TAG24 × GPBD4 RIL population, a 2.98 Mb (131.67–134.65 Mb) genomic region on chromosome A03, which overlaps with the region indicated in the present study to contain these two major ELS‐resistant QTLs (132.10–132.20 Mb and 133.65–133.73 Mb, respectively), was also found to contribute to LLS resistance (Pandey et al ., ). This supports the notion that this region on chromosome A03 has genes playing role in defence against leaf spots.…”
Section: Discussionmentioning
confidence: 97%
“…Disease resistance is a highly heritable trait of great value to crop production systems. Efforts have been made to identify the QTLs/candidate genes for important diseases such as ELS, LLS and TSWV in peanut (Khera et al ., ; Pandey et al ., ,). In the present study, 20 QTLs were identified on A‐subgenome LGs and 15 on B‐subgenome LGs.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, we need to have diagnostic markers with higher prediction accuracy and candidate genes with causal effect for a given trait. For trait discovery, instead of using a traditional mapping approach, it is possible now to use sequencing-based trait mapping approaches such as QTL-Seq, Bulk-Seq and Indel-Seq Pandey et al, 2017b). Similarly, recent advances in functional genomics such as gene expression atlases (Pazhamala et al, 2017) and use of near-isogenic lines for transcriptomics approaches can identify the candidate genes for the target traits.…”
Section: Integrated and Coordinated Approachmentioning
confidence: 99%
“…Through ddRADseq, high-throughput genotyping method using NGS technology, total 14,663 SNPs were developed and SNP-based genetic linkage map with 1,765 SNP markers was constructed. Pandey et al (2017) successfully applied QTL-seq approach based on whole-genome re-sequencing in peanut and allele-specific diagnostic markers were identified for three SNPs for rust resistance and one SNP for late leaf spot resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of peanut, reference sequences of two donor diploid species composing peanut have released in 2016 (1,211 Mb for A. duranensis and 1,512 Mb for A. ipaensis). Based on the diploid reference genome sequences, research focusing on identifying genes and SNP associated with important traits are underway (Bertioli et al 2016;Zhao et al 2016;Pandey et al 2017).…”
Section: Introductionmentioning
confidence: 99%